Exchange bias em multicamadas de NiFe/IrMn/Ta: um estudo através da magnetorresistência anisotrópica - Siqueira, Junara Villanova de (2015)
In this work a study of the exchange interaction between ferromagnetic (NiFe) and antiferromagnetic (IrMn) layers was done through structural, magnetic and electric characterization. NiFe/IrMn/Ta films were grown with different number of repetitions of this basic structure aiming to evaluate possible changes on the magnetic anisotropies presented by the samples. It was implanted in the Laboratório de Magnetismo e Materiais Magnéticos a system in order to measure the Anisotropic Magnetorresistance (AMR) as function of the applied field angle. The AMR consists in a change of the eletric resistance of a ferromagnetic material as function of the angle between the electric current and the magnetization of the material and, by this way, sensible to changes in the anisotropy presented by the samples. It is presented a simple model to calculate the AMR as function of the angle field and, by comparing with the experimental curves, to obtain the magnetic parameters who describe the system. In the model the equilibrium direction of the magnetization is obtained from the minimization of the free magnetic energy, which is given by the Zeeman, uniaxial, unidirectional and manetostatic energies. The AMR curves present an assymetry around 180 degrees when measured at fields below the bias one. According to the fittings, it was found that such assymetry can be due by a misalignment between the anisotropy axis (uniaxial and unidirectional) or by a misalignment between the measuring current and the easy magnetic axis of the samples. It was not observed, as expected, an expressive increase of the anisotropy dispersion of the uniaxial anisotropy with the increase of the number of trilayers. The same was observed with the bias and coercive fields.